Cooperation between Schools and Parents in the Learning of Visually Impaired Children - Rosyada Ayu Fatimah; Wahyu Sugiarto; Olvy Mailandari; Muhammad Afif Nur Tajudin; Difa’ul Husna (Journal Corner of Education, Linguistics, and Literature, 2023)
This article aims to raise awareness that it is important to collaborate between schools and parents in the education of blind children. Researchers will explain the definition of cooperation, the proper implementation of cooperation, constraints, and solutions that must be done when experiencing problems. This study uses field studies at SLB PGRI Sentolo, interview methods, and also literature studies. The results of this study prove that cooperation between schools and parents is needed in learning for blind children. The researcher also explained the findings that, in this collaboration, there must be some obstacles. But everything can be overcome by the tactics of teachers and parents.